Antibacterial and Antibiofilm Activity of Myrtenol against Staphylococcus aureus - Cordeiro, Laísa (Pharmaceuticals (Basel), 2020)
The increase in Staphylococcus aureus resistance to conventional antibacterials and persistent infections related to biofilms, as well as the low availability of new antibacterial drugs, has made the development of new therapeutic alternatives necessary. Medicinal plants are one of the main sources of bioactive molecules and myrtenol is a natural product with several biological activities, although its antimicrobial activity is little explored. Based on this, the objective of this study was to evaluate the antibacterial activity of myrtenol against S. aureus, determining the minimum inhibitory and bactericidal concentrations (MIC and MBC), investigating the possible molecular target through the analysis of molecular docking. It also aimed to evaluate the effect of its combination with antibacterial drugs and its activity against S. aureus biofilms, in addition to performing an in silico analysis of its pharmacokinetic parameters. Myrtenol showed MIC and MBC of 128 µg/mL (bactericidal action) and probably acts by interfering with the synthesis of the bacterial cell wall. The effects of the association with antibacterials demonstrate favorable results. Myrtenol has remarkable antibiofilm activity and in silico results indicate a good pharmacokinetic profile, which make myrtenol a potential drug candidate for the treatment of infections caused by S. aureus.